Analisis Organizational Citizenship Behavior (OCB) dan Work-Life Balance dalam Meningkatkan Kinerja Karyawan Generasi Z di PT Galang Tinggi Raya - Fajar, Gandi Muhammad (Jurnal EMT KITA, 2024)
Every company expects optimal employee performance to support the achievement of the company's main goals. This research aims to explore the impact of Organizational Citizenship Behavior (OCB) and Work-Life Balance on improving the performance of Generation Z employees at PT Galang Tinggi Raya. In addition, this research identifies supporting and inhibiting factors in improving the performance of Generation Z employees at PT Galang Tinggi Raya. This research involved a sample of 5 employees from PT Galang Tinggi Raya. The main approach in data collection is interviews as the primary method. The research results show that the implementation of OCB at PT Galang Tinggi Raya, especially in the aspect of Altruism (providing voluntary assistance to colleagues), has gone well. It was found that providing help to coworkers, both regarding tasks and personal problems, contributed positively to employee performance.